The Cambridge companion to pragmatism - Malachowski, Alan R. (Cambridge, United Kingdom Cambridge University Press, 2013)
"Pragmatism established a philosophical presence over a century ago through the work of Charles Peirce, William James and John Dewey, and has enjoyed an unprecedented revival in recent years owing to the pioneering efforts of Richard Rorty and Hilary Putnam. The essays in this volume explore the history and themes of classic pragmatism, discuss the revival of pragmatism and show how it engages with a range of areas of inquiry including politics, law, education, aesthetics, religion and feminism. Together they provide readers with an overview of the richness and vitality of pragmatist thinking and the influence that it continues to exert both in philosophy and other disciplines. The volume will be of interest to students and scholars of pragmatism, American philosophy and political theory"--Provided by publisher.
Machine generated contents note: Preface; Introduction: the pragmatic orientation; Part I. Classic Pragmatism: 1. 'Peirce's Principle' and the origins of pragmatism Christopher Hookway; 2. James' Holism: the human continuum Alan Malachowski; 3. Dewey's pragmatism: instrumentalism and meliorism David Hildebrand; Part II. Pragmatism Revived: 4. W. V. Quine: pragmatism within the limits of empiricism alone Isaac Nevo; 5. Hegel and pragmatism Richard Bernstein; 6. Heidegger's pragmatism redux Mark Okrent; 7. Practising pragmatist-Wittgensteinianism Phil Hutchinson and Rupert Read; 8. Putnam, pragmatism, and the fate of metaphysics David Macarthur; 9. Rorty's contribution to pragmatism: imagination over truth Alan Malachowski; Part III. Pragmatism at Work: 10. Feminism and pragmatism Marjorie C. Miller; 11. Education and the pragmatic temperament Carol Nicholson; 12. Dewey's pragmatic aesthetics: the contours of experience Garry L. Hagberg; 13. Pragmatism and religion Anton A. van Niekerk; 14. Radical pragmatism Michael Sullivan and Daniel J. Solove.
Includes bibliographical references (pages 345-366) and index.
Keywords: Pragmatism